Fundamentals of vehicle dynamics and modelling a textbook for engineers with illustrations and examples - Minaker, Bruce P. 1969- (Automotive series, 2020)
Fundamentals of Vehicle Dynamics and Modeling Bruce P. Minaker, University of Windsor, Canada An introduction to vehicle dynamics and the fundamentals of mathematical modeling Fundamentals of Vehicle Dynamics and Modeling is a student-focused textbook providing an introduction to vehicle dynamics, and covers the fundamentals of vehicle model development. It illustrates the process for construction of a mathematical model through the application of the equations of motion. The text describes techniques for solution of the model, and discusses the implications of the choice of method. It demonstrates how to conduct an analysis and interpret the results, and provides a foundation for understanding and predicting vehicle behaviour as a consequence of the design parameters. The book introduces the concept of multibody dynamics as applied to vehicles and provides insight into how vehicle dynamics concepts and tools are used in the automotive industry. Modeling the pneumatic tire is also covered, along with methods for solving the suspension kinematics problem, and prediction of acceleration and braking performance.